Mycobacterial Dormancy Systems and Host Responses in Tuberculosis - Peddireddy, Vidyullatha; Doddam, Sankara Narayana; Ahmed, Niyaz (Frontiers in Immunology, 2017)
Tuberculosis caused by the intracellular pathogen, Mycobacterium tuberculosis (Mtb) claims more than 1.5 million lives worldwide, annually. Despite promulgation of multipronged strategies to prevent and control tuberculosis, there is no significant downfall occurring in the number of new cases; and adding to this is the relapse of the disease due to the emergence of antibiotic resistance and the ability of Mtb to remain dormant after primary infection. The pathology of Mtb is complex and largely attributed to immune evading strategies that this pathogen adopts to establish primary infection, its persistence in the host and reactivation of pathogenicity under favorable conditions. In this review, we present various bio-chemical, immunological and genetic strategies unleashed by Mtb inside the host for its survival. The bacterium enables itself to establish a niche by evading immune recognition via resorting to masking, establishment of dormancy by manipulating immune receptor responses, altering innate immune cell fate, enhancing granuloma formation and developing antibiotic tolerance. Besides these, the regulatory entities such as DosR and its regulon, encompassing a variety of effector proteins play a key role in maintaining the dormant nature of this pathogen. Further, reactivation of Mtb allows relapse of the disease and is favored by the genes of the Rtf family and the conditions that suppress the immune system of the host. Identification of target genes and characterizing the function of their respective antigens involved in primary infection, dormancy and reactivation would likely provide vital clues to design novel drugs and / or vaccines to contain this disease at multiple levels.